Fruit and Vegetables for Sustainable Healthy Diets (FRESH); Work package 4 (WP4); World Vegetable Center, Arusha, Tanzania - Mwambi, Mercy; Ernest, Zablon; Mvungi, Henry (CGIAR System Organization, 2024)
The fruits and vegetable sector in Tanzania has grown significantly, increasing output 4.1 times from 1990 to 2020 (Reardon et al., 2024). However, post-harvest losses, accounting for 30-40% of annual crop production (MoA, 2019), hinder these gains. These losses are highest in the fruit and vegetable sector due to their perishability. This affects livelihoods by reducing farmers' income and threatens food and nutrition security.